“Transplant Research in Nonhuman Primates to Evaluate Clinically Relevant Immune Strategies in Organ Transplantation” - Fitch, Zachary (Transplant Rev (Orlando), 2019)
Research in transplant immunology using non-human primate (NHP) species to evaluate immunologic strategies to prevent rejection and prolong allograft survival has yielded results that have translated successfully into human organ transplant patient management. Other therapies have not proceeded to human translation due to failure in NHP testing, arguably sparing humans the futility and risk of such testing. The NHP transplant models are ethically necessary for drug development in this field and provide the closest analogue to human transplant patients available. The refinement of this resource with respect to colony MHC typing, reagent and assay development, and availability to the research community has greatly enhanced knowledge about transplant immunology and drug development.